Independence of Financial Performance of Jombang Regency Regional Government: - Sugeng Suprapto (ProBisnis : Jurnal Manajemen, 2022)
With regard to the granting of autonomy, regions are obliged to find alternative development funding without reducing the expectations of central government support. The purpose of this study was to analyze the ratio of financial independence of Jombang Regency in five years, namely 2016 to 2020.  This study uses qualitative descriptive methods. (especially the central and provincial governments) is very high. Data collection by observation and dokumkentasi. Data analysis by trianggulation. The results showed that the average ratio of independence of Jombang Regency for five years from 2016 to 2020 was 30% so that in the low category and showed a pattern of consultative relations this means that the level of regional dependence on external assistance